MANAJEMEN SUMBER DAYA MANUSIA DALAM PENINGKATAN MUTU PENDIDIKAN DI MADRASAH ALIYAH NEGERI 2 PANGANDARAN - Ani Ramayanti; Muchammad Erihadiana; Muhibinsyah Muhibinsyah (Universitas Islam Madura, 2023)
The management of educational institutions needs to be improved in order to progress and improve the quality of educational outputs and outcomes, both at the elementary to tertiary education levels, this is what later became the background for this research to be conducted by researchers. The main problems in this study are planning, organizing, human resource planning, supervision in improving the quality of education. The research method used is a qualitative approach by searching, analyzing, and making data interventions found in the field through interviews, observations and documents. Data analysis techniques are reducing, presenting and drawing conclusions. The results of the research are: 1) HR planning that is systematically designed based on school independence, 2) HR recruitment by prioritizing the principle of professionalism. 3) Selection must fulfill a professional element, 4) Training is carried out with an impact, a positive influence on schools, 5) Performance evaluation is carried out with quantitative-qualitative aspects. 6) Compensation. The efforts are to prepare educators through coaching, discussions, seminars, training, perfecting student recruitment strategies in promotions. The implication of this research is that institutional management is important to get serious attention so that the quality of education increases, therefore, education management needs to always be well-circulated so that it can give birth to a regulatory process that is also goo.